2021
DOI: 10.1111/jocd.14494
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical cysteamine hydrochloride in treating melasma: a systematic review

Abstract: Melasma is an acquired, chronic, and commonly recalcitrant hyper melanosis of the skin due to the hyperactivity of the epidermal melanocytes. It is described as bilateral brown-to-dark macules and patches mostly on sun-exposed areas, predominantly the face. 1,2 Melasma is presumed to be a multifactorial condition, not limited to any race, while being much more common in women, accounting for up to 90% of all cases predominantly with Fitzpatrick's skin phototypes III-V. 1 Since melasma negatively affects the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Many clinical investigations have demonstrated that topical application of cysteamine hydrochloride has no serious negative effects on the skin and is well tolerated at varied periods of administration 54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical investigations have demonstrated that topical application of cysteamine hydrochloride has no serious negative effects on the skin and is well tolerated at varied periods of administration 54 …”
Section: Discussionmentioning
confidence: 99%
“…9,12,13 Many clinical investigations have demonstrated that topical application of cysteamine hydrochloride has no serious negative effects on the skin and is well tolerated at varied periods of administration. 54 Several novel modalities and multimodality techniques have been tested to treat this psychologically damaging illness, including photoprotection, retinoid medicines, corticosteroids, salicylic and glycolic acid, tranexamic acid, melatonin, and glutathione. 55 So far, the evidence suggests that cysteamine cream can be used alone or in conjunction with other treatments to treat melasma.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…155,[172][173][174] However, a recent systematic review suggests that insufficient sample size, lack of long-term follow-up, and efficacy in cases with epidermal melasma only remain major limitations of clinical studies to draw a meaningful conclusion for the cysteamine's role in treating melasma that often remains unsatisfactorily treated. 175…”
Section: Cysteaminementioning
confidence: 99%
“…Although cysteamine formulations have shown significant decrease in MASI score after 4 months of application compared with placebo and even in a case resistant to Kligman's triple combination therapy, it was not found superior to 4% hydroquinonein or tranexamic acid mesotherapy in comparative trials 155,172–174 . However, a recent systematic review suggests that insufficient sample size, lack of long‐term follow‐up, and efficacy in cases with epidermal melasma only remain major limitations of clinical studies to draw a meaningful conclusion for the cysteamine's role in treating melasma that often remains unsatisfactorily treated 175 …”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
“…Hydroquinone is a first-line topical medical depigmentation therapy, that is used alone or in conjunction with other treatment modalities such as laser and or tranexamic acid [26][27][28]. Most documented treatments have primarily relied on the use of chemical methods [29][30][31][32], laser therapy [33][34][35][36][37][38], and topical creams [39][40][41][42][43]. However, the effectiveness of these treatment modalities is limited due to their adverse effects, especially in darker skin types [44].…”
Section: Introductionmentioning
confidence: 99%